Impact of Education on Health in Afghanistan: A Case of Kabul - Dariz, Karima (Integrated Journal for Research in Arts and Humanities, 2023)
The purpose of this study is to discover the impact of education on health in Afghanistan a case of Kabul through various review articles and authentic sites to elucidate that education and health have a strong correlation with each other in developing nations, especially in Afghanistan. In Kabul, there have been various inferior effects on the health sector in the past several years, roughly in 1995–2002, such as hypertension, mental diseases, nervous illnesses, deep depression, malnutrition, irritability, emphysema, or diabetes. In the period of 2003–2021, there have been reduced health illnesses due to an increasing education system for both females and males under the strongest inspirations. This study found that the education index has a high impact on life expectancy (health) through the estimation of HDI, and as the graduation of both male and female populations by estimation of one simple t-test is greater than the p-value in the 2021 year, its mean Accepted null hypothesis; hence, it has had a positive effect on education along with the health system as well as A two-way ANOVA of the enrollment of students in 2022 shows males have had a positive impact on the boosting of education and health, which bring prosperity to society; however, female enrollment has an inverse impact on education and healthcare. Lastly, the study examines indirect variables (third-party variables) that have impacted the health and healthcare system.